(untitled) (Doctor Virtualis, 2024)
In the Timaeus, Plato develops the story of Atlantis relying on the ideal State that Socrates creates in the Republic. The Atlantis’ myth is a discourse about the remote past of the excellent Athens, set at the time of the war against the island of Atlantis. The goddess Athena established a διακόσμησις for the political ordering of ancient Athens. With the διακόσμησις emerges the contact with the ideal state, because the order is based on the discourse Socrates produces in the Republic. Confirmation of this link comes from the Latin translation of the Timaeus by Calcidius, who distinguishes on the level of the substantia the story of Atlantis and then Timaeus’ discourse on the origin of the world; Calcidius’ translation reaches the School of Chartres, where William of Conches will define the story of Atlantis as an exemplum of the ideal State.